1993
DOI: 10.1016/0014-5793(93)80110-g
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin A2 and Δ12‐prostaglandin J2 induce apoptosis in L1210 cells

Abstract: Treatment of L1210 cells with prostaglandin A2 (PGA2) or 9‐deoxy‐Δ9,12‐13,14‐dihydro PGD2 (Δ12‐PGJ2) resulted in significant G2/M arrest and subsequent DNA fragmentation at concentrations that are cytotoxic to the cells. On agarose gel electrophoresis, DNA ladder formation was evident 24 h after the addition of Δ12‐PGJ2 and remained apparent through 72 h, whereas G2/M accumulation was observed 6 h after the treatment. When the morphology of cells was examined by electron microscopy, L1210 cells incubated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(47 citation statements)
references
References 35 publications
2
45
0
Order By: Relevance
“…yclopentenone prostaglandins (CyPG) are naturally occurring eicosanoids that display varied biological activities, including antiviral (1) and antitumoral effects (2), modulation of the heat shock response (3), and induction of oxidative stress (4) and apoptosis (5). The CyPG of the J 2 series, such as 15-deoxy-⌬ 12,14 -prostaglandin J 2 (15d-PGJ 2 ), arise from the spontaneous dehydration of PGD 2 , whereas PGA 2 is produced by PGE 2 dehydration.…”
mentioning
confidence: 99%
“…yclopentenone prostaglandins (CyPG) are naturally occurring eicosanoids that display varied biological activities, including antiviral (1) and antitumoral effects (2), modulation of the heat shock response (3), and induction of oxidative stress (4) and apoptosis (5). The CyPG of the J 2 series, such as 15-deoxy-⌬ 12,14 -prostaglandin J 2 (15d-PGJ 2 ), arise from the spontaneous dehydration of PGD 2 , whereas PGA 2 is produced by PGE 2 dehydration.…”
mentioning
confidence: 99%
“…Cyclopentenone prostaglandins, especially 15-deoxy-D 12,14 -prostaglandin J 2 (15d-PGJ 2 ), have been shown to exert antineoplastic effects on various types of human cancer (Kim et al, 1993;Ahn et al, 1998;Clay et al, 1999;Keelan et al, 1999;Butler et al, 2000;Chang and Szabo, 2000;Clay et al, 2001;Straus and Glass, 2001). These effects, frequently attributed to activation of peroxisome proliferator-activated receptor gamma (PPARg), have been recently proven to be at least partially mediated through PPARg-independent pathways (Clay et al, 2001(Clay et al, , 2002Straus and Glass, 2001;Hsiang and Straus, 2002;Liu et al, 2003).…”
mentioning
confidence: 99%
“…Thus, cyclin D1 expression and S-phase entry were induced by prostaglandin F2α in Swiss 3T3 fibroblasts, whereas other prostaglandins were able to arrest cells at the G2/M phase of the cell cycle. 49,50 We have shown that cPLA 2 activity increased transiently during mid-G1 phase of the ongoing cell cycle of CHO and neuroblastoma N2A cells, this activity being dependent upon the activity of p42/44. 51,52 By using different inhibitors of cPLA 2 , it was demonstrated that the activity of cPLA 2 in mid-G1 phase was required for entry into S phase.…”
Section: A the Map Kinase Pathwaymentioning
confidence: 95%